NT Insights Vol 1.1 Addition on Natural Numbers
We have already seen how the 5 axioms together generate the entire set of natural numbers N in Vol 1.0. Now we will define a binary operation, called addition, on N in terms of those 5 axioms.
Before that, let us give these elements of N their usual names, as follows:
- s(0)=1
- s(s(0))=s(1)=2
- s(s(s(0)))=s(s(1))=s(2)=3
and so on…
An important observation is that the successive natural numbers differ by a single reference to s(). Let us call a reference to s() as a unit distance. Then, clearly, the successive natural numbers are unit distance apart. Also, the difference between any two natural numbers is a multiple of this unit distance.
Another important observation is that 0 does not involve any reference to function s(). This is so because all other numbers are successors of 0, but 0 is not successor of any natural number (Reminds me of Lord Shiva, who is called Anaadi). The magnitude of distance, therefore, can not be assigned to 0. Whereas, for every non-zero natural number b, its distance from 0 = number of calls to s() needed to produce b.
Thus, when we say that a natural number is b, we actually mean that this natural number is b units away from 0.
We observe that every successor of 0 derives its magnitude (or value), relative to 0, the magnitude of 0 itself is null (∵0 is the reference point or origin of all its successors). A consequence of this is that, when we include the magnitude (distance) of 0 into distance of another natural number, say b, then the total distance still is equal to b. This leads us to define addition as follows:
Addition: Define a mapping +:N×N→N as
a+0:=a ∀a∈N
a+s(b):=s(a+b) ∀a,b∈N
Putting b=0 in (1.1), we get a+s(0)=a+1=s(a+0)=s(a).
Thus, s(a)=a+1 ∀a∈N, which is as expected because successive natural numbers are unit distance apart.
Notice that:
2:=s(1) is a definition, whereas
1+1=1+s(0)=s(1+0)=s(1) is a theorem (derived by applying definitions).
Proposition 1.2: Equations (1.1) and (1.2) define addition (m+n) for all m,n∈N.
Proof: We need to show that the mapping (m,n)→(m+n) is defined ∀ (m,n)∈N×N. Consider an arbitrary natural number m∈N. If we show that (m+n) is definied for all n∈N, then we are done (∵ m being arbitrary, spans entire N).
But, we have to prove this by using the 5 axioms and nothing else. The property (m+n)∈N has to be satisfied for all n∈N. So let us consider the set of all n satisfying this property. Define S={n∈N:(m+n)∈N}. Since we have to prove the result for all n∈N, we can just show that S=N.
To show this equivalence, inductive axiom (5th axiom) can be employed.
0∈S (∵m+0∈N by definition (1.0)).
Assume n∈S⟹(m+n)∈N.
Then, m+(n+1)=m+s(n)=s(m+n)∈N (∵(m+n)∈N; use invariance of s()).
⟹(n+1)∈S
Thus, by inductive axiom of Peano, S=N. ◼
Proposition 1.3 (Associativity of Addition): For all a,b,c∈N, we have a+(b+c)=(a+b)+c.
Proof: Assume a,b∈N to be arbitrary, i.e., (a,b) spans N×N. Define set
S={c∈N:a+(b+c)=(a+b)+c}.
Now if we show that S=N, then we are done (Compare this proof strategy with that in Proposition 1.2).
0∈S, because
LHS: (a+b)+0=(a+b) and RHS: a+(b+0)=a+(b)
⟹ LHS=RHS..
Assume c∈S⟹a+(b+c)=(a+b)+c.
Then, LHS: a+(b+s(c))=a+s(b+c)=s(a+(b+c)) and
RHS: (a+b)+s(c)=s((a+b)+c)=s(a+(b+c)) ∵(c∈S).
⟹ LHS=RHS.
Hence, by induction axiom of Peano, S=N. ◼
By definition we know that a+0=a; since we haven’t proved commutativity of addition yet, we don’t know that 0+a=a at this point.
Lemma 1.4: For all a∈N, 0+a=a.
Proof: Following previous strategies, we define
S={a∈N:0+a=a}. Now we need to show that S=N.
Observe that, 0+0=0. So, 0∈S.
Assume that a∈S⟹0+a=a.
Then, 0+s(a)=s(0+a)=s(a) (∵a∈S).
⟹s(a)∈S.
Hence, by inductive axiom, S=N. ◼
Lemma 1.5 For all x,y∈N, we have s(x)+y=x+s(y).
Proof: Consider arbitrary x∈N. Define the set
S={y∈N:s(x)+y=x+s(y)}.
Now we need to show that S=N.
x+s(0)=s(x+0)=s(x)=s(x)+0.
Thus, 0∈S.
Assume, y∈S, i.e., s(x)+y=x+s(y).
Then, s(x)+s(y)=s(s(x)+y)=s(x+s(y)) (∵y∈S).
=x+s(s(y)).
⟹s(x)∈S.
Thus, by inductive axiom, S=N. ◼
Comments
Post a Comment